The Role of Sensory Processing Sensitivity and Self-management on Quality of Life in Multiple Sclerosis - Babak Bakhshayesh Eghbali; Mozaffar Hosseini-Nejad; Sajjad Saadat; Masoome Babaee; Kimia Eyvani; Kosar Kohandel; Masoud Shabani Chobe (Caspian Journal of Neurological Sciences)
Background: Multiple sclerosis (MS) symptoms lead to functional impairments that predict limitations, unemployment and withdrawal from social or leisure activities and affect the health-related quality of life (HRQOL). Sensory processing sensitivity (SPS) and self-management are important factors affecting HRQOL in people with MS. Objectives: We decided to determine the role of SPS and self-management in predicting HRQOL in MS patients. Materials & Methods: This cross-sectional-analytical study was conducted on 320 relapsing-remitting MS patients registered in the nationwide MS registry of Iran (NMSRI), Guilan Province, from March 2020 to March 2021. The SPS questionnaire (SPSQ), MS self-management scale-revised (MSSM-R) and 36-item short-form survey (SF-36) were used to collect data. Results: The findings showed that quality of life in people with MS has a positive significant relationship with SPS (r=0.14) and self-management (r=0.22) (P<0.05). The results of the multiple regression model also showed that the MSSM-R and SPSQ explained a total of 12% of the variance of the SF-36. Conclusion: Overall, SPS and self-management are factors affecting the quality of life of MS patients.